Alkylation of Benzene with Ethanol over ZSM-5 Based La–P Catalysts - Sabit Eyyub Mamedov; Aynur Abulfat Iskenderova; Eyyub Sabit Mammadov; Nargiz Firudin Akhmedova; Fuad Shamsaddin Kerimli; Sevda Baba Ismayilova (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Benzene ethylation in the presence of HZSM-5 zeolites is a promising method for producing ethylbenzene. This study examined the effects of modifying lanthanum and phosphorus as additives to the HZSM-5 catalyst, tested in the temperature range of 300-500 °C, at a benzene to ethanol molar ratio of 2:1 in a hydrogen stream. The influence of promoters on acidity and pore structure was investigated using X-ray Diffraction (XRD), NH3 Temperature Programmed Desorption (NH3-TPD), Scanning Electron Microscope (SEM), Brunauer, Emmett, and Teller (BET), and Barrett-Joyner-Halenda (BJH). Among 4%La samples, 4%P/HZSM-5 demonstrated higher ethylbenzene selectivity and operational stability associated with a decrease in the density of strong acid sites and an increase in zeolite mesoporosity because of modification. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).